(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Crystal ionicity is one of the very important parameter concerning semi-conducting materials. Crystal ionicity can be used in tackling problems related to various fields in solid state physics as well as chemistry such as crystal structure, band structure, elastic constants, alloys problems, effective charges, cohesive energies, heat of formation, micro hardness etc.Within the framework of a classical model, an ionic crystal is regarded as composed of independently polarizable ions. The dielectric polarization in ionic solids is of two types (i) electronic and (ii) ionic. The polarization arising from the displacement of electron clouds of ions with respect to their nuclei is known as electronic polarization. In addition to this, the displacements of ions from their equilibrium configurations give rise to ionic Polarizability. Both these polarizations contribute to the dielectric constant at low frequencies i.e. in the infrared region. At high frequencies corresponding to the optical region the contribution of ionic displacement polarization becomes almost negligible due to large inertia of ions. The dielectric constant at such frequencies is known as electronic or optical dielectric constant ε∞ and arises entirely due to electronic polarization .The dielectric constant at low frequencies is known as static dielectric constant εo .It is one of the remarkable feature of ionic crystals that ε0 for these crystals differs appreciably from ε∞, values of εo is significantly larger than ε∞ .The relationship between ε∞ and electronic polarization is known as Lorentz-Lorenz (LL) relation. The relationship between static dielectric constant εoand corresponding Polarizabilities is known as the Claussius – Mossotti (CM) relation. The LL and CM relations along with the equation of motion for ions lead to the Szigeti relation [129]. The dielectric constants have also been related to the optical mode frequencies, viz. short-range Interionic forces [122-127].